Iš baltų amatininkystės istorijos: baltiški Berlock kabučiai - Bliujienė, Audronė (Archaeologia Lituana, 2005)
The distribution, origin and chronology (Bla-b/B2) of gold bcrloks in Scandinavia, Jutland Peninsula and on Zealand, Funen, Öland and Bomholm islands are known well enough (Fig. 1). Gold berloks as isolated finds were spread in the south-eastern part of Norway, Mecklenburg and the huge territory between the rivers Elbe and the Vistula (Fig. 1). Gold berloks make some concentration in Wielbark culture in the Gdańsk Bay and the Vistula delta regions (Fig. 1; Table 1: 1-11). Gold berloks in Wielbark culture arc known from the first part of the 2nd century and the first decades of the 3rd century (B1/B2b/C1 periods) Germanic jewellers like to produce gold bowl and pear shaped berloks, which belong to the three main types in the classification proposed by Adrian Müller. Already the first gold berloks gave an idea to the jewellers of Wielbark culture to transform technologically complicated golden berloks into much simpler bronze berloks (Fig. 2: IV a-b).Golden berloks and the first hand adaptations of these pendants made inside Wielbark gave an impulse to Baltic jewellers to produce bronze ornaments of the same type, but using technologies available in the eastern Baltic region during the Roman period. Baltic jewellers were not in a state fit to produce granules, filigree wire and to use soldering. Therefore Baltic jewellers started producing berloks with a cluster of granulation at the underneath of a pendant by casting (Fig. 2). Filigree work totally disappeared form the berlok’s surface, and only notches adorn the loop of the pendant, which might give an illusion of filigree work. Consequently, already in the B2-C1a-b bronze berloks receive a first transformation. which was made by Baltic jewellers in the West Lithuanian Stone Circle Graves culture (Fig. 1: 2:IV:1; 7-9; table 1). Transformed bronze berloks immediately got a lot of different imitations and very quickly receded even from pendants transformed in the Baltic area (Fig. 2:IV: 2-4: 3-11).In A. Müller’s classification, Baltic berloks belong to the fourth type. However, the variability of Baltic bronze berloks allows dividing them into four subtypes (Fig. 2). To the IV: 1 subtype might be ascribed bowl-shaped bronze berloks. To the subtypes IV:2-4 belong berloks with a straight backside and underneath more or less similar to the cross (Figs. 2; 3). Baltic bronze berloks lost the general idea of the berlok, because they were used in strings with glass or enamel beads and bronze pendants of different types. Such fashionable ornaments were worn by Baltic ladies (Figs. 8-9; 10:4; 11:5). Bronze Baltic berloks are dispersed in a big area of the Eastern Baltic region (Fig. 1; Table 1). One pendant of this type was found in Tarand culture in the northern part of Estonia.Bronze berloks of type IV first subtype were in use at the end of the 2nd century till the beginning of the 3rd century. There are no big chronological differences between type IV and its subtypes 2-4. Pendants of these subtypes might be ascribed to the first part of the 3rd century or the middle of the 3rd century. Probably the latest date for bronze Baltic berloks in the Eastern Baltic region is the late 3rd century.Bronze berloks of the type IV first subtype were produced by handicraftsmen of Western Lithuanian stone circle grave culture. Other subtypes of Baltic bronze berloks had been produced in the areas where they were found.Bronze berloks, like some other types of Germanic ornaments, made a rather considerable influence on the development of Baltic jewellery, mostly on the ornaments that used bronze granules and a fictitious filigree technique (rosette pins and brooches, necklaces with a capsule-shaped clasp) (Fig. 12:3-4). Granules and fictitious filigree technique were adopted for creation of ornaments of specific Baltic style during the late Roman period.